Global hydro-environmental lake characteristics at high spatial resolution - Bernhard Lehner; Mathis L. Messager; Maartje C. Korver; Simon Linke (Scientific Data, 2022)
Measurement(s) hydro-environmental characteristics • lake • water body • hydrographic feature Technology Type(s) digital curation Sample Characteristic - Environment freshwater environment • aquatic environment Sample Characteristic - Location Earth (planet)